(untitled) (Comprehensive Journal of Science, 2025)
This study aims to analyze the prevalence of urinary tract infections (UTIs) and identify the bacterial pathogens responsible for them, with a specific focus on Escherichia coli among patients attending Sabratha Teaching Hospital during the study period. A total of 756 urine samples from both males and females were examined. The results showed that 256 samples (33.86%) were positive for UTI, while 500 samples (66.13%) were negative. The findings also revealed that females were more susceptible to infection than males, with 184 cases (24.33%) recorded among females compared to 72 cases (9.52%) among males. Bacterial culture results demonstrated that Escherichia coli was the most prevalent uropathogen, accounting for 16.13% of all samples, surpassing other isolated bacteria such as Klebsiella spp, Proteus spp, Pseudomonas spp, Enterobacter spp, in addition to Gram-positive bacteria. The study further indicated that adults aged 21–50 years had the highest infection rates, while winter recorded the highest seasonal prevalence, suggesting the influence of biological and environmental factors on infection patterns. These findings confirm that UTIs represent a common and significant health problem, particularly among females and adults, and that E. coli remains the primary causative agent. Therefore, the study emphasizes the need to strengthen public health awareness, promote preventive practices, and continuously monitor antibiotic susceptibility patterns to ensure effective treatment and limit the emergence of antimicrobial resistance.